I Know It Is Not Real (And That Matters) Media Awareness vs. Presence in a Parallel Processing Account of the VR Experience - Hartmann, Tilo; Hofer, Matthias (Frontiers in Virtual Reality, 2022)
Inspired by the widely recognized idea that in VR, not only presence but also encountered plausibility is relevant (Slater, 2009), we propose a general psychological parallel processing account to explain users' VR and XR experience. The model adopts a broad psychological view by building on interdisciplinary literature on the dualistic nature of perceiving and experiencing (mediated) representations. It proposes that perceptual sensations like presence are paralleled by users' media awareness or their belief that "this is not really happening." We review the developmental underpinnings of media awareness, and argue that it is triggered in users’ voluntarily exposure to VR, as well as by encountered sensory and semantic (in)consistencies. Our account sketches media awareness and presence as two parallel processes that together define a situation as a media exposure situation. We discuss how both might mutually influence each other. We also review potential joint effects on subsequent psychological responses that characterize the user experience. We conclude the article with a programmatic outlook on testable assumptions and open questions for future research.